2018
DOI: 10.1016/j.biopsych.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small-Molecule Inhibitors of Protein Kinase C Epsilon Reduce Ethanol Consumption in Mice

Abstract: These results identify lead compounds for development of PKCε inhibitors that reduce alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Our results not only highlight the relevance of PKCα in the control of the transcriptional regulation of genes relative to the nPKCs in lung cancer cells, but also unveil the intricacies in the biological patterns controlled by the DAG pathway. Due to the widespread implications of phorbol ester/DAG receptors in cancer, neurological and cardiovascular disorders 3,6264 , the generation of C1 domain ligands with distinctive specificity may represent promising therapeutic leads and pharmacological tools for dissecting the pathophysiological basis of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our results not only highlight the relevance of PKCα in the control of the transcriptional regulation of genes relative to the nPKCs in lung cancer cells, but also unveil the intricacies in the biological patterns controlled by the DAG pathway. Due to the widespread implications of phorbol ester/DAG receptors in cancer, neurological and cardiovascular disorders 3,6264 , the generation of C1 domain ligands with distinctive specificity may represent promising therapeutic leads and pharmacological tools for dissecting the pathophysiological basis of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of CRF to CeA slices increases presynaptic GABA release in a CRF1, but not CRF2, -dependent manner (Kang-Park et al , 2015; Nie et al , 2004; Roberto et al , 2010). The effects of CRF on inhibitory neurotransmission in the CeA are regulated in part by protein kinase C-epsilon (PKCε); PKCε knockout mice exhibited increased baseline GABAergic tone in the CeA but were not responsive to the acute effects of exogenous CRF application, and PKCε inhibition occluded the effects of acute CRF in wild type mice (Bajo et al , 2008; Blasio et al , 2017). CRF has also been shown to alter excitatory transmission within the CeA.…”
Section: Crf and Amygdala Microcircuitrymentioning
confidence: 99%
“…Binge-like alcohol drinking, in which non-dependent subjects achieve a high blood-alcohol concentration during a limited window of alcohol access, has been shown to increase expression of PKCε in the CeA, and inhibition of PKCε specifically within the CeA reduced alcohol consumption in the binge model (Cozzoli et al , 2016). Given that PKCε has been shown to mediate some of the effects of CRF and alcohol on CeA GABAergic activity (Bajo et al , 2008; Blasio et al , 2017), the relationship between PKCε, CRF1 signaling and alcohol consumption warrants further investigation. If indeed native PKCε serves to inhibit GABAergic activity in the CeA, the acute increase in PKCε expression following sub-chronic alcohol exposure may represent a compensatory mechanism to offset the acute enhancement of GABAergic signaling induced by alcohol.…”
Section: The Crf System Fear and Alcohol In The Amygdalamentioning
confidence: 99%
“…Given evidence for the role of PKCε in AUD, a recent study tested several novel molecules that act as PKCε inhibitors. They found that two compounds inhibited PKCε with Ki <20 nM, were highly selective of PKCε, crossed the bloodbrain barrier, prevented alcohol-stimulated GABA release in the central amygdala, and reduced alcohol consumption in an intermittent 24-hour access, two-bottle choice drinking paradigm in wild-type but not in Prkce -/mice (18).…”
Section: Promising Molecular Targetsmentioning
confidence: 99%